Technology of fresh herbs storage using hydrogel and antioxidant composition - Priss, Оlesia; Прісс, Олеся Петрівна; Присс, Олеся Петровна; Євлаш, В. В.; Eвлаш, В. В.; Yevlash, V. (My University, 2017)
EN:There is a stable consumer demand for fresh culinary herbs. Also, the greenery contains a large number of valuable phytonutrients. Despite high efficiency and increasing annual production of fresh herbs, the problem of preserving their quality in the post-harvest period remains unresolved. Because of the high specific surface area of evaporation, in the green crops droop quickly, they lose their marketable quality, and, as a result, the level of profitability of greenery production in general is being reduced. It is necessary to use new effective approaches to leafy greens storage in order to reduce product losses during transportation and storage.
Keywords: storage; сulinary herbs; leafy greens; hydrogel; antioxidants; marketable quality; ascorbicacid; chlorophylls; carotenoids